2018
DOI: 10.5944/openpraxis.10.4.889
|View full text |Cite
|
Sign up to set email alerts
|

‘Dark reuse’: an empirical study of teachers’ OER engagement

Abstract: There is scant evidence of OER reuse or sharing; OER apologists maintain that reuse is happening in private spaces, but others argue there is no evidence of such ‘dark reuse’.The OER lifecycle provides a model of OER engagement, defining five key practices: finding, composing, adapting, reusing and sharing. However, no empirical research has yet investigated whether teachers’ engagement with OER follows this model; evidence from OER repository analytics suggests not.This paper draws on an empirical study of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 27 publications
1
48
0
9
Order By: Relevance
“…Although over the years the conceptual understanding of OER has improved, more insights are needed on teachers' practices with OER (Beaven, 2018;Schuwer and Janssen, 2018). This study aimed to explore teachers' practices and to elicit the need for support to foster OER adoption within a Dutch University of Applied Sciences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although over the years the conceptual understanding of OER has improved, more insights are needed on teachers' practices with OER (Beaven, 2018;Schuwer and Janssen, 2018). This study aimed to explore teachers' practices and to elicit the need for support to foster OER adoption within a Dutch University of Applied Sciences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, this does not imply that reuse is not happening, as it might take place 'below the radar' (Glennie, Harley and Butcher, 2012). A recent study by Beaven (2018) showed that most practices are hidden and that adoption most often takes place in what Wiley (2009) has called ' dark reuse'. Teachers either find resources somewhere online, receive resources from their colleagues or already have resources in their personal collections.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas formal changes, such as linguistic adaptations, predominate (Beaven, 2018), content-related adjustments affect deleting and arranging of content. Specifically, with open textbooks, less content is added and hardly ever remixed (Hilton III, Lutz, & Wiley, 2012).…”
Section: Literature On the 5 R'smentioning
confidence: 99%
“…According to the remix problem, there is little empirical evidence that OER components involving processing and mixing of materials are realised (Wiley, Bliss, & McEwen, 2014). Other studies, in turn, see the OER cycle anchored in teachers' practice (Beaven, 2018). Thus, it remains open to what extent remixing takes place and is not answered within empirical studies.…”
Section: Literature On the 5 R'smentioning
confidence: 99%
“…Although the benefits of OER in education have been proved [21,22], the use of OER seems to be low in higher education [23][24][25]. Nevertheless, it does not mean that the reuse of these resources is not happening.…”
Section: Lifelong Learning and Oermentioning
confidence: 99%